Características semânticas de mentiras no Português Brasileiro: uma análise gradual - Colosso, Carolina Peternela (Universidade Federal de São Carlos, 2024)
The aim of this research is to analyze the semantic components of the concept of lying in contemporary Brazilian Portuguese (BP), and to defend a definition of this concept based on the idea of prototypes. To this end, we applied the questionnaire on the semantic features that make up lies proposed by Coleman & Kay (1981) to speakers of BP. The anonymous response to this questionnaire, whose subjects are adult native speakers of BP, will lead to a characterization of the prototype of lying in BP. Once we have this characterization, we compare the data obtained by applying this questionnaire to English speakers, looking for intercultural differences in lying, as well as analysing the implications of the results obtained for BP with philosophical descriptions of lying, which, in general, do not take empirical data for their discussion. Thus, this research contributes not only to the description of the concept of lying in BP, but also to the beginning of a translinguistic evaluation of this concept and its implications in the philosophical debate. Finally, we would like to highlight the originality of this research, given that there is practically no work on the subject in BP linguistics.
Semantic characteristics of lies in Brazilian Portuguese: a gradual analysis
Keywords: Semântica; Mentira; Gradualidade; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA